An evaluation approach of the communication error risk of a metro operation team based on the cloud model. - Niu, Chenxu; Niu, Ke; Zhang, Yaqiong; Liu, Wenbo; Zhang, Jia; Wang, Lei; Du, Yihang; Sidorenko, Valentina Gennadyevna (International Journal of Occupational Safety & Ergonomics, 2025)
Problems in aspects including team structure, team members' collaboration, personality differences and language application ability can potentially give rise to communication failures of the entire team and systemic risks. Scant studies have focused on the distinctive risk factors of communication errors and the methods for quantifying these risks. For Zhengzhou metro, critical event technology is employed to construct the factors influencing the risk of communication error of the metro operation team, i.e., interpersonal risk, language application risk and external risk. The analytic hierarchy process (AHP) is utilized to assign weights to each index, and the cloud model is adopted to evaluate the risk of communication error quantitatively. The results indicate that the risks were in the order of interpersonal > external > language application, and the main contributing factors are the risks of information management (U13), global awareness (U14), parallel task processing (U32) and time pressure (U34).